SISTEMA MUNICIPAL DE ENSINO: UMA ANÁLISE DA MUNICIPALIZAÇÃO DA EDUCAÇÃO EM TEIXEIRA DE FREITAS-BA - Bissaro, Debora Zago (2019)
This dissertation had as object of study the Municipal System of Education, through the administrative decentralization of the actions of the State by the bias of the municipalization of elementary education in the city of Teixeira de Freitas-BA. The main